Unlocking the genetic secrets of Dorper sheep: insights into wool shedding and hair follicle development - Yuan, Xiaochun; Meng, Ke; Wang, Yayan; Wang, Yifan; Pan, Cuili; Sun, Haoran; Wang, Jankui; Li, Xinhai (Frontiers in Veterinary Science, 2024)
Dorper sheep is popular among farming enterprises with strong adaptability, disease resistance, and roughage tolerance, and an unique characteristic of natural shedding of wool. In a large number of observations on experimental sheep farms, it was found that the wool of some sheep still had not shed after May, thus manual shearing was required. Therefore, understanding the molecular mechanisms of normal hair follicles (HFs) development is crucial to revealing the improvement of sheep wool-related traits and mammalian skin-related traits. In this study, transcriptome analysis was performed on skin tissues of adult Dorper ewes in the shedding (S) and non-shedding (N) groups in September 2019, January 2020, and March 2020, respectively. The results identified 3,278 differentially expressed transcripts (DETs) in the three comparison groups within the S group, 720 DETs in the three comparison groups within the N group, and 1,342 DETs in the three comparison groups between the S-vs-N groups. Time-series expression analysis revealed 2 unique expression patterns in HF development, namely, elevated expression in the anagen phase (A pattern) and the telogen phase (T pattern). DETs with stage-specific expression had a significant presence in processes related to the hair cycle and skin development, and several classic signaling pathways involved in sheep HF development, such as Rap1, estrogen, PI3K-Akt, and MAPK, were detected. Combined analysis of DETs, time-series expression data, and weighted gene co-expression network analysis identified core genes and their transcripts influencing HF development, such as DBI, FZD3, KRT17, ZDHHC21, TMEM79, and HOXC13. Additionally, alternative splicing analysis predicted that the isoforms XM_004004383.4 and XM_012125926.3 of ZDHHC21 might play a crucial role in sheep HF development. This study is a valuable resource for explaining the morphology of normal growth and development of sheep HFs and the genetic foundation of mammalian skin-related traits. It also offers potential insights into factors influencing human hair advancement.